Dehydrosqualene Desaturase as a Novel Target for Anti-Virulence Therapy against Staphylococcus aureus - Peng Gao (American Society for Microbiology, 2017)
ABSTRACT Staphylococcus aureus, especially methicillin-resistant S. aureus (MRSA), is a life-threatening pathogen in hospital- and community-acquired infections. The golden-colored carotenoid pigment of S. aureus, staphyloxanthin, contributes to the resistance to reactive oxygen species (ROS) and host neutrophil-based killing. Here, we describe a novel inhibitor (NP16) of S. aureus pigment production that reduces the survival of S. aureus under oxidative stress conditions. Carotenoid components analysis, enzyme inhibition, and crtN mutational studies indicated that the molecular target of NP16 is dehydrosqualene desaturase (CrtN). S. aureus treated with NP16 showed increased susceptibility to human neutrophil killing and to innate immune clearance in a mouse infection model. Our study validates CrtN as a novel druggable target in S. aureus and presents a potent and effective lead compound for the development of virulence factor-based therapy against S. aureus. IMPORTANCE S. aureus staphyloxanthin contributes substantially to pathogenesis by interfering with host immune clearance mechanisms, but it has little impact on ex vivo survival of the bacterium. Agents blocking staphyloxanthin production may discourage the establishment and maintenance of bacterial infection without exerting selective pressure for antimicrobial resistance. Our newly discovered CrtN inhibitor, NP16, may offer an effective strategy for combating S. aureus infections.